Pembuatan Aplikasi Virtual Maket Rumah Berbasis Android - Donny Susanto; Rolly Intan; Erandaru Erandaru (Jurnal Infra, 2017)
Property or house is one thing that will not be endless in the market of buying and selling. Often buyers come to a property exhibition to find the house they want. Today, there are so many ways that sellers do / provide to attract buyers. One of them is providing a mock-up.A mock-upt is an artificial form of a house to be formed using a certain scale and is usually made of wood, styrofoam, paper, clay, and other media.However, the mock-up itself has a drawback that is not can not be visualized or imagined on a scale of 1: 1. The technology that developed in the present time allows to eliminate the deficiency by realizing the maket innovation in the form of visual so that the satisfaction and purpose of a model more obtained.